The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1464-5491.2010.02983.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of microalbuminuria in young people with Type 1 diabetes: importance of age and diabetes duration

Abstract: Aims To determine the occurrence of microalbuminuria in young people with Type 1 diabetes mellitus followed prospectively for 2 years and to relate the presence of persistent elevations in urinary albumin excretion (UAE) to age, diabetes duration, puberty and other factors. Methods During a 2 year period, random urine samples were obtained from 471 patients, aged 8–18 years (mean ± SD 12.9 ± 2.3 years) with Type 1 diabetes duration 5.6 ± 3.0 years, as part of routine clinical care. Urine albumin and creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 27 publications
4
55
5
Order By: Relevance
“…Other studies have reported similar results: the prevalence rate of microalbuminuria was estimated to be 5.9% in children with a mean age of 12.7 years and a diabetes duration of 5.1 years (4). Another study in children (mean age 12.9 years) has revealed that persistent microalbuminuria was present in 9.3% (13). The present survey also showed that intermittent microalbuminuria was not a predictive factor for the progression of microalbuminuria and that in a real-world setting, intermittent microalbuminuria has little prognostic significance in adolescents with type 1 diabetes (1,4,12,14).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other studies have reported similar results: the prevalence rate of microalbuminuria was estimated to be 5.9% in children with a mean age of 12.7 years and a diabetes duration of 5.1 years (4). Another study in children (mean age 12.9 years) has revealed that persistent microalbuminuria was present in 9.3% (13). The present survey also showed that intermittent microalbuminuria was not a predictive factor for the progression of microalbuminuria and that in a real-world setting, intermittent microalbuminuria has little prognostic significance in adolescents with type 1 diabetes (1,4,12,14).…”
Section: Discussionsupporting
confidence: 62%
“…Several cross-sectional studies demonstrated that 6-25% of patients between 15 and 20 years of age develop microalbuminuria (1,4,8,9,10). Because the natural history of microalbuminuria in adolescents with type 1 diabetes is often not as consistent and clear as in adults, there is ongoing discussion about predictors of persistent microalbuminuria and nephropathy (4,8,11,12,13). Some studies have shown that half of the probands with type 1 diabetes and microalbuminuria have normoalbuminuria at the end of puberty (4,11).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies even higher percentages of both have been found [43]. Significant association between the occurrence of microalbuminuria or proteinuria and poor glucose control has been confirmed [26,43]. In addition to poor glycemic control, clinical markers of insulin resistance were associated with its development [44].…”
Section: Microalbuminuria In Different Childhood Diseasesmentioning
confidence: 86%
“…Microalbuminuria was most extensively investigated in children with both type 1 and type 2 diabetes [25,26] and its significant role established. In recent years its assessment has been utilized as a screening test for the presence of diabetes-related kidney disease [38].…”
Section: Microalbuminuria In Different Childhood Diseasesmentioning
confidence: 99%
See 1 more Smart Citation